Assessing the Effectiveness of Public Investment in Research and Development by Federal Executive Bodies in Russia - Ilina, Irina; Zharova, Elena; Borodin, Aleksandr; Burlankov, Stepan (Olsztyn Economic Journal, 2016)
The purpose of this study is to develop an instrument to measure the effectiveness of public investment in R&D and make timely adjustments to scientific and technical policy. This will contribute to the growth of fundamental results, patents as well as their commercialization and innovative development for the overall economy. This article assesses the effectiveness of public investment in research and technological development (RTD), including attracted extra-budgetary funds, on the basis of the authors’ methodology for assessing the efficiency of public spending on RTD projects. The main distributors of state budget funds in Russia are the Federal Executive Bodies (FEB). The proposed tool first allows the evaluation of the effectiveness of public expenditure on RTD in general, although it does not involve comparing individual FEB administrations, but only evaluates their work in promoting the development of their assigned research areas in terms of dynamics. This method sets the general rules for an evaluation of effectiveness in the state financial support of RTD, defines the key indicators reflecting the performance of such support and the use of science as a tool for ensuring the achievement of indicators and the socio-economic development of the state.